(untitled) (ELECTRICAL MACHINES, MATERIALS AND DRIVES — PRESENT AND TRENDS, 2021)
The three-phase induction machine mathematical model presented in the paper is adequate for applying to the deep rotor bars case. The rotor resistance and its leakage inductivity depend upon the rotor currents frequency because of the skin effect. Following the previous considerations, one developed slip-dependent analytical expressions of the rotor circuit resistance, respectively rotor circuit leakage reactance. A modified space phasor-based mathematical model of the deep bar induction motor is tested through simulations to assess the motor’s characteristics. The results follow the literature.